Combined Blockade of GARP:TGF-β1 and PD-1 Increases Infiltration of T Cells and Density of Pericyte-Covered GARP+ Blood Vessels in Mouse MC38 Tumors - Bertrand, Charlotte; Van Meerbeeck, Pierre; de Streel, Grégoire; Vaherto-Bleeckx, Noora; Benhaddi, Fatima; Rouaud, Loïc; Noël, Agnès; Coulie, Pierre G.; van Baren, Nicolas; Lucas, Sophie (Frontiers in Immunology, 2021)
When combined with anti-PD-1, monoclonal antibodies (mAbs) against GARP:TGF-β1 complexes induced more frequent immune-mediated rejections of CT26 and MC38 murine tumors than anti-PD-1 alone. In both types of tumors, the activity of anti-GARP:TGF-β1 mAbs resulted from blocking active TGF-β1 production and immunosuppression by GARP-expressing regulatory T cells. In CT26 tumors, combined GARP:TGF-β1/PD-1 blockade did not augment the infiltration of T cells, but did increase the effector functions of already present anti-tumor T cells. Here we show that, in contrast, in MC38, combined GARP:TGF-β1/PD-1 blockade increased infiltration of T cells, as a result of increased extravasation of T cells from blood vessels. Unexpectedly, combined GARP:TGF-β1/PD-1 blockade also increased the density of GARP+ blood vessels covered by pericytes in MC38, but not in CT26 tumors. This appears to occur because anti-GARP:TGF-β1, by blocking TGF-β1 signals, favors the proliferation of and expression of adhesion molecules such as E-selectin by blood endothelial cells. The resulting densification of intratumoral blood vasculature probably contributes to increased T cell infiltration and to the therapeutic efficacy of GARP:TGF-β1/PD-1 blockade in MC38. We conclude from these distinct observations in MC38 and CT26, that the combined blockades of GARP:TGF-β1 and PD-1 can exert anti-tumor activity via multiple mechanisms, including the densification and normalization of intratumoral blood vasculature, the increase of T cell infiltration into the tumor and the increase of the effector functions of intratumoral tumor-specific T cells. This may prove important for the selection of cancer patients who could benefit from combined GARP:TGF-β1/PD-1 blockade in the clinics.